(untitled) (Swiss Medical Weekly, 2020)
The discovery and administration of exogenous insulin has revolutionised diabetes treatment and continues, almost 100 years on, to be the basis for the management of insulin deficiency. However, insulin therapy still has potentially life-threatening side effects such as hypoglycaemia and increased risk of cardiovascular disease. So far, improvements in insulin therapy have focused mainly on modulating its pharmacokinetic and pharmacodynamic properties and improving delivery methods, while variations in the insulin sensitivity of peripheral tissues has received relatively little attention. Notably, tissue insulin sensitivity has been shown to vary considerably around the clock, which could contribute greatly to the effect (and risk of side effects) of a given dose of insulin. Recent evidence suggests that photic inputs regulate diurnal variations in the insulin sensitivity of metabolically relevant tissues via a previously unrecognised mechanism involving the ventromedial hypothalamic nucleus. Therefore, understanding the mechanisms underlying photic control of insulin action is of paramount medical importance. In addition, considering “when” (i.e., the time of day) could assist in deciding “how much” insulin should be administered and hence could aid the fine-tuning of insulin dosage, lowering the risk of side effects, and improving the quality of life of patients with insulin deficiencs.